PAYROLL SYSTEM IN. PARTNER WITH ENDOWMENT USING MICROSOFT VISUAL BASIC 6.0 - Yanti Yanti; Elly Agustina J, SKom, MMSI Elly Agustina J, SKom, MMSI (Jurnal Sistem Informasi, 2008)
Scientific research aims to create a payroll system on PT. Mitra Abadi, ranging fromdata input to the preparation of reports using Microsoft Visual Basic 6.0.This research is a scientific research by collecting data. The author obtained thesedata by conducting interviews related to the employees at the companyFrom this research we can conclude that by using computerized will gain the ease andspeed up the process of calculating employees' salaries as well as making monthlyreports.